Witchcraft and welfare : spiritual capital and the business of magic in modern Puerto Rico - Romberg, Raquel (University of Texas Press, 2003)
[Publisher-supplied data] "This book makes an important addition to the literature on magic and spirits in the modern world. ... In comparison with other well-known anthropological works on magic and modernity, this stands out on account of its skill at evocation, at getting inside people and events and not merely using them as examples or 'case studies.'"--Michael Taussig, Professor of Anthropology, Columbia University Persecuted as evil during colonial times, considered charlatans during the nation-building era, Puerto Rican brujos (witch-healers) today have become spiritual entrepreneurs who advise their clients not only in consultation with the spirits but also in compliance with state laws and new economic opportunities. Combining trance, dance, magic, and healing practices with expertise in the workings of the modern welfare state, they help lawyers win custody suits, sick employees resolve labor disability claims, single mothers apply for government housing, or corporation managers maximize their commercial skills. Drawing on extensive fieldwork among practicing brujos, this book presents a masterful history and ethnography of Puerto Rican brujería (witch-healing). Raquel Romberg explores how brujería emerged from a blending of popular Catholicism, Afro-Latin religions, French Spiritism, and folk Protestantism and also looks at how it has adapted to changes in state policies and responded to global flows of ideas and commodities. She demonstrates that, far from being an exotic or marginal practice in the modern world, brujería has become an invisible yet active partner of consumerism and welfare capitalism